Degradation of phenol by a catalytic ozonation - Palaniappan, Yogeswary (2006)
Screening on the catalytic ozonation of phenol over zeolite-based catalyst i.e Beta and ZSM-5 was investigated under room temperature condition using a semi continuous system. The degree of degradation of 100ppm of phenol was measured on the treated samples. The results showed that the performance of Beta was better than ZSM-5 with the degradation of phenol of 67.4 and 49.0%, respectively after 90 minutes of reaction time. In addition, the degradation of phenol was higher in the presence of both catalysts compared to without any catalyst. Further screening of beta catalyst impregnated with ferum and titanium showed that the degradation of phenol was slightly increased with the presence of Fe-beta compared to Ti-beta catalyst. Thus, Fe-beta was furthered subjected to different experimental variables such as ozone gas flow rate, temperature and pH of phenol solution, mass and metal weight percent impregnated in the catalyst, concentration and the volume of phenol to be treated. It was observed that a smaller percentage of metal loading catalyst resulted a higher degradation compared to those with higher metal loading catalyst. As expected, the degradation of phenol increases with ozone flow rates and mass of catalyst. Interestingly, the degradation of phenol was significantly high under basic condition where the degradation was almost complete i.e 98.1% at initial pH 11. On the contrary, the degradation of phenol decreases with increasing temperature, concentration and volume of phenol solution.